Clinical dilemma-management of low rectal cancer in a Jehovah’s Witness - Chik, Azhani; Md Nor, Azmi; Ong, Li Wei, David (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Jehovah’s Witness followers pose a clinical dilemma to the medical practitioners due to their religious belief of an absolute prohibition of blood transfusion under any circumstances. We present a case of Jehovah’s Witness follower who underwent an ultra-low anterior resection for rectal cancer after neo-adjuvant chemo-radiotherapy. The challenges in the perioperative management are highlighted and managed accordingly.